The efectiveness of interactive multimedia courseware in developing student’s selfenlightening level - Hamzah, Rohana; Md. Isa, Kamarudzaman (Penerbit UTM Press, 2010)
The Faculty of Art and Design (FSSR), UiTM Shah Alam was formed based on a holistic education mission. However, the main problem occurred especially in inculcating spiritual values among arts and design students. Therefore, the purpose of this study is to offer an alternative approach to conventional practice in teaching and learning of art and design by developing, integrating and evaluating spiritual-development interactive multimedia courseware and study its’ impact on students self-enlightening level. In order to measure the effectiveness of this interactive multimedia courseware an instrument has been developed and the alpha value is 0.93. The quantitative research method of true experimental pretest-posttest design has been applied. The under-graduate arts and design students in semester three have been chosen as the population of study because the actual design process only begins during this semester of their study program at FSSR. 101 students have been involved in the study. A comparison between the experimental group and the control group shows that there was a significant difference in the self-enlightening level. The mean values for experimental group (interactive multimedia approach group) (4.18) are higher compared to the control group (3.94). This finding also indicates that current practice in arts and design education at the faculty was unable to improve self-enlightening level among art and design students. However, using the interactive multimedia technology can help develop self-enlightening level among them.